Tel Tsaf, Israel: Die Arbeiten des Jahres 2013 - Klimscha, Florian (e-Forschungsberichte des DAI, 2023)
The prehistoric settlement Tel Tsaf, situated near Beth Shean in the middle Jordan Valley, is excavated by an international team of scientists. The work started in 2013 with a test campaign that could verify the existence of very well preserved Late Neolithic/Middle Chalcolithic remains with no later disturbances right under the top-soil. Soundings in the west of the site could document a much larger settlement area than previously thought. The stratigraphy continues to the Neolithic Wadi Rabah-culture and thus offers the unique situation to examine the beginnings of early forms of social complexity. The project aims to document this stratigraphy and analyse the socioeconomic changes involved in this process in an interdisciplinary perspective.